High‐Harmonic Optical Vortex Generation from Photonic Bound States in the Continuum. Issue 1 (27th October 2021) - Kang, Lei; Wu, Yuhao; Ma, Xuezhi; Lan, Shoufeng; Werner, Douglas H.
Abstract: Stemming from bound states in the continuum (BICs), momentum‐space polarization vortices observed in photonic structures provide an attractive approach to generating optical vortex (OV) beams. On the other hand, dominated by the selection rules, the harmonic generation from nanostructures exhibits a nonlinear geometric phase that depends on both the harmonic orders and the handedness of circularly polarized harmonic signals. Here, the third‐ and fifth‐harmonic optical vortex generation from an amorphous silicon photonic crystal slab, supporting the guided resonance associated with BICs at near infrared wavelengths, is numerically demonstrated. The results show that, determined by the nonlinearity phase, the topological charge ( lnω ) associated with the n th‐harmonic OV beams follows σ( n ∓1) q, where q is the polarization charge of the BIC and the ∓ sign represents the opposite or same polarization of the n th‐harmonic signal relative to the circular polarization state (σ) of the fundamental waves. Exploiting harmonic multiplexing, this approach can significantly improve the channel capacity of OV generators based on topologically protected optical BICs. Abstract : High‐harmonic optical vortex (OV) generation from a photonic crystal slab supporting the resonance associated with bound states in the continuum is demonstrated. The topological charge of the generated odd‐order n th‐harmonic OV beams follows lnω = σ( n ∓1) q, where ∓ represents the opposite or same polarization of the n th‐harmonic signal relative to the circular polarization state (σ) of the fundamental waves.